The Role of House of Sustainability in Green Supply Chain Management to Support Eco-Friendly Crystal Salt Packaging Design - Bagaskara, Tegar Winoto; Pulansari, Farida (Newinera Publisher, 2025)
This study aims to develop an environmentally friendly crystal salt packaging design using the House of Sustainability (HoS) approach at PT Baruna Energi Solusindo Teknik. The methods used include observation, questionnaire distribution, and literature study to identify consumer needs through Voice of Customer (VoC), as well as mapping sustainability attributes with Quality Function Deployment (QFD). The analysis showed that the use of HDPE plastic in packaging results in high carbon emissions and energy consumption. Based on VoC, the most prioritized attributes for consumers are environmental health, safety, and product price. The most influential technical responses in packaging design are the type of eco-friendly material, product durability, and pollution control. The proposed alternative packaging uses kraft paper material with a size of 33 cm × 33.5 cm and a transparent window to display the product contents. This design is considered to fulfill the overall technical, aesthetic, and sustainability aspects. In conclusion, the implementation of the House of Sustainability is effective in supporting environmentally friendly packaging design and strengthening green supply chain management in the company.